2013
DOI: 10.1099/vir.0.048553-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy reconstructions of triatoma virus particles: a clue to unravel genome delivery and capsid disassembly

Abstract: Triatoma virus (TrV) is a member of the insect virus family Dicistroviridae and consists of a small, non-enveloped capsid that encloses its positive-sense ssRNA genome. Using cryo-transmission electron microscopy and three-dimensional reconstruction techniques combined with fitting of the available crystallographic models, this study analysed the capsids corresponding to mature and several RNA-empty TrV particles. After genome release, the resulting reconstruction of the empty capsids displayed no prominent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 36 publications
6
30
0
Order By: Relevance
“…Dimers of pentamers of capsid protein protomers very similar to the crystallized form of IAPV capsid proteins (Fig. 6) were previously observed as disassembly products of TrV (56). The two pentamers are held together by interactions of residue His61 of VP2 with Val11 from the N terminus of VP1 and of Gln65 from VP2 with Asp198 from VP3 (Fig.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Dimers of pentamers of capsid protein protomers very similar to the crystallized form of IAPV capsid proteins (Fig. 6) were previously observed as disassembly products of TrV (56). The two pentamers are held together by interactions of residue His61 of VP2 with Val11 from the N terminus of VP1 and of Gln65 from VP2 with Asp198 from VP3 (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The genome release of many picornaviruses results in the formation of empty capsids, the so-called B particles (54). However, the empty capsids of some picornaviruses and dicistroviruses disassemble into pentamers of capsid protein protomers (55, 56). Furthermore, pentamers of capsid protomers were also shown to be capsid precursors (57, 58).…”
Section: Resultsmentioning
confidence: 99%
“…These picornavirus entry steps can be mimicked in the laboratory setting by heating infectious particles to produce A-particle and 80S. Heating TrV virus particles has also been shown to release the genome, resulting in a stable empty capsid (24).…”
mentioning
confidence: 99%
“…The TrV capsid structure was solved at high resolution (10), and it was shown to be composed of 60 copies of the three major structural proteins (VP1, VP2, and VP3), all of which are folded in a jelly roll-like core. Surprisingly the small protein VP4 (5.5 kDa) was not observed either in the X-ray crystallographic structure or in cryo-electron microscopy (cryo-EM) three-dimensional reconstructions (10,11), even though it is known to be present in infectious TrV particles (8). These data showed that the TrV VP4 protein is disordered within the capsid, contrary to picornavirus VP4, which is largely ordered inside the particle in a manner that matches the icosahedral capsid symmetry (12,13).…”
mentioning
confidence: 99%
“…Moreover, empty capsids (after genome delivery) do not display any conformational changes similar to those in picornaviruses (11). Therefore, a different mechanism of uncoating was proposed by characterizing the capsid disassembly and genome release using atomic force microscopy (AFM) and native mass spectrometry techniques (22).…”
mentioning
confidence: 99%